Growth performance of juvenile Oreochromis niloticus fed with Rhizoclonium riparium var. implexum supplemented diets - Cabanero, Paulo C. (Miagao, Iloilo University of the Philippines Visayas, 2016)
Two (2) nutrition were conducted to investigate the effects of dietary protein levels and supplemental Rhizocloniumriparium var. implexum raw meal (RRM) and its protein concentrate (RPC) on the growth performance, feed efficiency, nutrient utilization and body composition of juvenile Nile tilpia, Oreochromisniloticus. Four experimental diets (based on the composition of a practical diet) were formulated to contain a range of crude protein 33-36% for RRM and 35-37% for RPC. The dried raw algae (RRM) repalaced soybean meal by weight at 0% (Control diet), 15% (Diet 2), 30% (Diet 3) and 45% (Diet 4) equivalent to inclusion rates of 0%, 4.2%, 8.4% and 12.6%, respectively. Experiment 2 (RPC) consisted of a basal diet (Diet 1) containing no Rhizoclonium and crystal lysine requirement, a diet with RPC replacing 30% of soybean meal supplemented with crystal lysine at 1.0% (Diet 2), a diet with RPC replacing 30% supplemented with lysine at 1.5% (Diet 3) and a diet with RPC replacing 45% of soybean meal and 3.0% lysine. The experimental diets were fed to four replicated groups of Nile tilapia at a rate of 2 times daily for 16 weeks. This study showed that Rhizocloniumriparium var. implexum meal was highly acceptable and could replace the imported soybean meal in the culture of the Nile tilapia. Replacement rate that could be used was 45%, equivalent to 12.6% dietary inclusion. Also the protein concentrate of this seaweed can be improved by Lys supplementation, and the practical level recommended for inclusion and supplementation was 30% replacement of soybean meal with 1.0% Lys.
Thesis (M.S. Fisheries-Aquaculture) -- Miagao, Iloilo : University of the Philippines Visayas, January 2016.
Keywords: Oreochromis niloticus; Rhizoclonium riparium var. implexum protein concentrate (RPC).; Rhizoclonium raw meal (RRM).; Soybean meal; Lysine